Processing Low-Grade Retted Straw of Fibre Flax Into Homogeneous Fiber Using Trailed Flax-Harvesting Combine КВЛ-1 - E. V. Soboleva; A. V. Bezbabchenko; V. G. Vnukov; S. V. Prokofiev (Сельскохозяйственные машины и технологии)
To obtain long and short flax fiber of high quality under the conventional processing technology, retted flax straw of no less than grade 1.5 is required. However, according to some data, low-grade retted straw flax of grade 0.75 and lower used at some flax-processing plants can make up to 30 percent of the total mass of harvested raw materials. To maintain profitability, this retted straw must be processed into short homogenous fiber using new innovative technologies and equipment. (Research purpose) Study of the technological process of primary processing of low-grade retted straw flax, starting from the field and finishing at a flax-processing plant in various technological lines, determination of the rational composition of technological equipment of post-treatment lines of chaff -fiber mass obtained in the field with the flax-harvesting combine KVL-1, as well as determination of quality indicators of the obtained fiber. (Materials and methods) For research purpose, two types of low-grade retted straw were used as raw material: type 1 – retted straw grade1.0, type 2 – retted straw no.0.5, taken from Russian flax-processing plants. Primary processing of retted straw was carried out directly in the field with the flax-harvesting combine KVL-1. Further, the resulting chaff -fiber mass was transported to the laboratory and cleaned in the stationary conditions in various lines consisting of commercially available disintegrator DLV-2 and tow shakers with a lower gilling section. (Results and discussion) Analysis of the research results has revealed that the raw material used – low-grade retted flax straw – features low strength and high separability of fiber. The authors have put forward some recommendations on using the technology of processing low-grade retted flax straw into homogeneous fiber. (Conclusion) The authors have described the design of two technological lines for processing low-grade retted flax straw according to the ‘field-plant’ pattern. Using these lines, one can produce homogeneous flax fiber (monofilament) with an average mass length of 189-195 millimeter, a linear density of 5.6-6.2 Tex and a mass fraction of chaff of 6.7-16.7 percent. It is emphasized that the proposed technologies allow obtaining homogeneous fiber of a grade not exceeding 2 from low-grade retted flax straw. This type of fibre can be used to produce between-joisting and volumetric sealants, nonwoven materials, modified flax fibre, cellulose, technical and medical cotton wool, low-grade yarn, composites, etc.